Analisa Faktor Penyebab Kemacetan Lalu Lintas di Jalan Kolektor Studi Kasus Jalan Gajah Mada Gunung Pangilun Kota Padang - Maiyozzi Chairi; Jihan Melasari; Rian Afandi (Universitas Putra Indonesia YPTK Padang, 2020)
Congestion is a situation or state of stalling or even stopping traffic caused by a large number of vehicles exceeding road capacity. Traffic congestion is a big problem that is often faced in Indonesia, especially in big cities. This study aims to analyze the factors that cause congestion in Jalan Gajah Mada Gunung Pangilun, Padang City. This research is quantitative descriptive by calculating traffic volume and the causes of traffic jams. And following the Urban Road Capacity Guidelines (PKJP, 2014). Based on the results of the field survey in Road Capacity (C) 3340 pcu / hour, Total Traffic Volume (Q) 1446 pcu / hour and Saturation Degree (DJ) 0.43 pcu / hour, so that the Road Service Level (LOS) type can be obtained B in the sense that traffic flow is stable, the speed starts to be influenced by traffic conditions, but can still be chosen according to the will of the driver. The highest level of congestion occurs on Wednesday, December 11, 2019 (from the day surveyed).